Vegan vs Paleo: Carbon Footprints and Diet Quality of 5 Popular Eating Patterns as Reported by US Consumers (P03-007-19). (13th June 2019) - O'Malley, Keelia; Willits-Smith, Amelia; Aranda, Rodrigo; Heller, Martin; Rose, Diego
Abstract: Objectives: The food system contributes substantially to current environmental problems, which has prompted researchers to evaluate both environmental as well as nutritional impacts of dietary choices. However, there has been no research on the impacts of popular diets as consumed in the US. This study estimated the carbon footprint and diet quality of popular diets as selected by a nationally representative sample of US consumers. Methods: The 2005–2010 National Health and Nutrition Examination Survey (NHANES) 24-hour recall data were used to categorize individual adult diets ( N  = 16, 800) into one of six mutually exclusive dietary patterns: vegan, vegetarian, pescatarian, paleolithic, and ketogenic. All other diets were classified into an omnivore pattern. Food groups in the USDA Food Patterns Equivalent Database were used to define these patterns. For example, the vegan pattern was defined as those who did not consume meat, seafood, eggs or dairy, and the paleo pattern included those who did not eat grains, legumes or dairy. Average daily greenhouse gas emissions (GHGE) in carbon dioxide equivalents per 1000 kilocalories (kg CO2 -eq 1000 kcal −1 ) were calculated by matching our previously developed database of Food Impacts on the Environment for Linking to Diets (dataFIELD) to NHANES individual diet data. Diet quality was determined using the Healthy Eating Index 2010 (HEI). Ordinary least-squares regression was used to assess differences in diet patterns. Results: The most frequent 1-day diet patterns were omnivore (87%), pescatarian (7%), and vegetarian (6%). The lowest carbon footprint diets were vegan (mean = 1.0 kg CO2-eq 1000 kcal-1), vegetarian (1.1), and pescatarian (1.9), and the highest footprints were omnivore (2.3), paleo (2.8) and keto (4.2). These average carbon footprints for the vegan, vegetarian, and pescatarian patterns were significantly lower ( p  < .05) than that of the omnivore pattern, and the keto pattern was significantly higher. Average HEI scores for the vegetarian and pescatarian patterns were significantly higher compared to the omnivore pattern, and the keto and paleo patterns were significantly lower. Conclusions: These data support the growing body of research identifying the environmental benefits of plant-based diet patterns and identify the environmental cost of other popular diet patterns in the US. Funding Sources: Wellcome Trust.